Respuesta :

Answer:

Step-by-step explanation:

i am in 7th grade sorry can't help. I don't know what those signs mean.

Step-by-step explanation:

g(t) = (412 - 6t + 9) dt

To find g'(t), we need to differentiate each term with respect to t separately:

g'(t) = d/dt (412) - d/dt (6t) + d/dt (9)

Since the derivative of a constant term is zero and the derivative of a constant multiplied by t is the constant itself, we have:

g'(t) = 0 - 6 + 0

Therefore, g'(t) = -6.

To find g'(3), substitute t = 3 into the derived expression:

g'(3) = -6

Hence, g'(3) = -6

mark me as brilliant

ACCESS MORE